Successful Transplantation in ABO‐ and HLA‐Incompatible Living Kidney Transplant Patients: A Report on 12 Cases. Issue 5 (13th April 2016) - Rostaing, Lionel; Karam, Béatrice; Congy‐Jolivet, Nicolas; Hage, Valérie; Sallusto, Federico; Esposito, Laure; Doumerc, Nicolas; Debiol, Bénédicte; Guilbeau‐Frugier, Céline; Game, Xavier; Allal, Asma; Kamar, Nassim
Abstract: Few studies have assessed the outcomes of ABOi/HLAi living‐kidney transplantation. We report a single‐center experience of 12 ABOi/HLAi living‐kidney recipients. Twenty‐seven donor‐specific alloantibodies (DSAs) (1–6 per patient) were found with fluorescence intensities of 1500–15 000. Desensitization was based on IVIg, two doses of rituximab (375 mg/m 2 ), tacrolimus‐based (0.2 mg/kg) immunosuppression (started on day‐10 pretransplant), and 11 (6–27) pretransplant apheresis sessions (plasmapheresis, specific or semi‐specific immunoadsorption). By day 0, 17 of the 27 DSAs had become undetectable. After 19 (3–51) months, patient‐ and graft‐survival rates were 100% and 91.6%, respectively. One patient had an acute humoral rejection whereas three had a chronic antibody‐mediated rejection (CAMR). At the last follow‐up, kidney biopsies were nearly normal in seven cases (58.3%) and renal function was excellent except for the three cases of CAMR. Four patients had a BK virus infection. We conclude that ABOi/HLAi living‐kidney transplantation is a reasonable option for highly sensitized patients.